2006
DOI: 10.1016/j.jphysparis.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A free energy principle for the brain

Abstract: By formulating Helmholtz's ideas about perception, in terms of modern-day theories, one arrives at a model of perceptual inference and learning that can explain a remarkable range of neurobiological facts: using constructs from statistical physics, the problems of inferring the causes of sensory input and learning the causal structure of their generation can be resolved using exactly the same principles. Furthermore, inference and learning can proceed in a biologically plausible fashion. The ensuing scheme res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
799
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,096 publications
(826 citation statements)
references
References 40 publications
22
799
0
5
Order By: Relevance
“…Otherwise, assembling and memorizing experiences would be pointless, as they would loose their capacity to guide successful behavior as soon as a one-time breach of expectation had occurred. Hence, the divergent perception should not cause instantaneous adaptation of the internal model; accordingly, a process of adaptation is revealed by diminution of the neural correlate of divergence over a large number of iterations (Friston, Kilner, & Harrison, 2006;Grill-Spector, Henson, & Martin, 2006;Majdanžić, Bekkering, van Schie, & Toni, 2009) as targeted in the adaptation contrast (ii). It has previously been established that the cortical motor network is capable of predicting the ongoing course of action (Jeannerod, 1995).…”
Section: Adaptation In the Cortical Motor Networkmentioning
confidence: 99%
“…Otherwise, assembling and memorizing experiences would be pointless, as they would loose their capacity to guide successful behavior as soon as a one-time breach of expectation had occurred. Hence, the divergent perception should not cause instantaneous adaptation of the internal model; accordingly, a process of adaptation is revealed by diminution of the neural correlate of divergence over a large number of iterations (Friston, Kilner, & Harrison, 2006;Grill-Spector, Henson, & Martin, 2006;Majdanžić, Bekkering, van Schie, & Toni, 2009) as targeted in the adaptation contrast (ii). It has previously been established that the cortical motor network is capable of predicting the ongoing course of action (Jeannerod, 1995).…”
Section: Adaptation In the Cortical Motor Networkmentioning
confidence: 99%
“…It has been suggested that we have "epistemic needs" to have order and regularity in the world around us (Kruglanski, 1980). Indeed, it has been proposed that the structure of brain networks are fundamentally non-random and modular in nature (Sporns, 2011), and at a functional level, a general organizing principle of the brain is to minimize unpredictability between the external environment and internal states (Friston, Kilner, & Harrison, 2006;Friston, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the definition of P by Equation (3) differs from the one referred to by the free-energy principle (Nicolis and Prigogine, 1977;Haken, 1983;Friston et al, 2006;Friston, 2010), the idea is the same: Evolution of any kind directs toward a free energy minimum state. The least-time principle parallels also of the principle of least effort (Zipf, 1949).…”
Section: Annilamentioning
confidence: 99%